Maximizing Zakat Revenues in the COVID-19 Period - Umar Habibu Umar; Mustapha Abubakar (International Journal of Zakat, 2021)
The Novel Coronavirus (COVID-19) pandemic has put the entire world into not only health but economic and social problems. Currently, finding a sustainable way out of the poverty caused by the pandemic had become a global concern. Unfortunately, even as poverty alleviation has for long been a key issue in the agenda of OIC member countries, the emergence of the pandemic has pushed down these countries into a poverty hole deeper than before. Islamic social finance instruments, particularly zakat, waqf and Islamic microfinance are believed to be valid instruments that could mitigate the consequences of the pandemic. Against this, the present study aims to provide a way of maximizing zakat revenues in OIC member countries through the creation of zakat accounting standards. The study found only two existing zakat accounting standards for the computation of business zakat. The first one was developed by AAOIFI in 1998 and became effective in 1999, primarily for the application by IFIs. Given the limitation and inappropriate application of AAOIFI’s zakat accounting standard in the Malaysian context, the Malaysian Accounting Standard Board developed another standard suitable for the application by Malaysian firms effective from 2016. Thus, the foregoing findings imply the need for each OIC member country to create the zakat accounting standard to adopt by its firms in order to maximize zakat revenues.